2014
DOI: 10.12945/j.aorta.2014.14-020
|View full text |Cite
|
Sign up to set email alerts
|

Acute Type A Dissection Repair in an Achondroplastic Dwarf: Anesthetic, Perfusion, and Surgical Concerns

Abstract: In this report we present a 43-year-old male with achondroplastic dwarfism who presented with acute Type A aortic dissection with aortic insufficiency. The patient underwent successful Bentall and hemiarch repair. Anesthetic, perfusion-related, and surgical planning and execution are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Following intubation, intravascular access and patient positioning are both challenging due to short limbs, reduced joint mobility, and anatomy of the chest (8). Several reports note the use of ultrasound guidance for intravascular access and arterial and vein cut-downs for safe vascular exposure (10,11). These differences from the general population must be considered in preparing for procedures on patients with achondroplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following intubation, intravascular access and patient positioning are both challenging due to short limbs, reduced joint mobility, and anatomy of the chest (8). Several reports note the use of ultrasound guidance for intravascular access and arterial and vein cut-downs for safe vascular exposure (10,11). These differences from the general population must be considered in preparing for procedures on patients with achondroplasia.…”
Section: Discussionmentioning
confidence: 99%
“…For procedures requiring artery or vein conduit, it should be noted that saphenous vein graft may be challenging to obtain, too short for purposes of a bypass, or unsuitable for bypass. One such report noted smaller length of saphenous vein harvest with moderate quality due to patient anatomy and performed a three-vessel coronary-artery bypass with both right and left internal mammary arteries (10). Another report noted a 29 cm saphenectomy incision that extended to the patient's ankle (12), and a third noted pre-operative phlebography to assess for vein quality (13).…”
Section: Discussionmentioning
confidence: 99%
“…Scafuri et al used a pediatric cannula for aortic valve replacement with root enlargement in a 56-year-old woman with achondroplasia; however, they encountered no problem during CPB [ 6 ]. Other studies have reported using adult cannulas for the repair of type A aortic dissection [ 7 ], aortic valve replacement [ 8 ], and pulmonary endarterectomy [ 9 ]. Despite no consensus on this matter, an adult cannulation can often be performed successfully and should be considered given that these studies reportedly mentioned increasing their CPB flow to maintain adequate tissue perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, although the patient did not receive CSF drainage, he still fully recovered. Al-Jughiman et al [ 13 ] previously reported 1 male case of achondroplastic dwarfism who presented with acute type-A aortic dissection with aortic insufficiency. He underwent Bentall and hemiarch repairing surgery.…”
Section: Discussionmentioning
confidence: 99%